KENDALA PELAKSANAAN KURIKULUM 2013 - Sufian Husni Salam; Abd Mukti; Syamsu Nahar (Sekolah Tinggi Agama Islam Al Hidayah, 2014)
Curriculum is an important component in education, from elementary school, high school and university. Function of curriculum for another goal, for examples: goal of nation, goal of school and goal of social resource development. In Indonesia, there is transformation of curriculum, whereas transformation of curriculum must be in ten years as role. Currently, in the fact, transformation of curriculum before ten years like in Orde Baru Government. Transformation of KTSP curriculum to 2013 curriculum at Bambang Sudibyo Minister and Muhammad Nuh as Education Minister. Realization of 2013 curriculum in school is rush. There are many government weakness for prepare teacher guide book and student guide book, so realization of curriculum has not maximum. Therefore, the school must work hard to realize 2013 curriculum.